2021
DOI: 10.11113/jurnalteknologi.v83.15080
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Desulfurization of Dibenzothiophene by Pseudomonas Sp. Strain Kwn5 Immobilized in Alginate Beads

Abstract: Biodelfurization of petroleum has emerged as a potential alternative to the hydrodesulfurization and oxidative desulfurization processes. However, the main obstacle in its commercial application is the efficiency and practicality of using bacterial cells. Pseudomonas sp. strain KWN5 was tested for the ability to use dibenzothiophene (DBT) in n-tetradecane as the sole sulfur source with two phase oil-water system. The biodesulfurization ability of strain KWN5 was evaluated by immobilized cells with dibenzothiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Desulfurization of DBT by immobilized bacteria has been measured in other studies using the disappearance of DBT rather than the production of 2-HBP as an end point (Gunam et al, 2021;Guo et al, 2014;Guobin et al, 2005;Peng & Wen, 2010). These studies used initial DBT concentrations similar to those used in the work T A B L E 1 Enhancement (%) of the maximum 2-HBP produced by immobilized and nanoparticle-coated 32O-W and 32O-Y strains at 0.1 and 0.5 mmol l −1 initial DBT and DBTS compared to that produced under the same conditions by planktonic cells (Sar et al, presented here and found, as seen here with both DBT and DBTS, large decreases in residual DBT during culturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desulfurization of DBT by immobilized bacteria has been measured in other studies using the disappearance of DBT rather than the production of 2-HBP as an end point (Gunam et al, 2021;Guo et al, 2014;Guobin et al, 2005;Peng & Wen, 2010). These studies used initial DBT concentrations similar to those used in the work T A B L E 1 Enhancement (%) of the maximum 2-HBP produced by immobilized and nanoparticle-coated 32O-W and 32O-Y strains at 0.1 and 0.5 mmol l −1 initial DBT and DBTS compared to that produced under the same conditions by planktonic cells (Sar et al, presented here and found, as seen here with both DBT and DBTS, large decreases in residual DBT during culturing.…”
Section: Discussionmentioning
confidence: 99%
“…Desulfurization of DBT by immobilized bacteria has been measured in other studies using the disappearance of DBT rather than the production of 2‐HBP as an end point (Gunam et al, 2021; Guo et al, 2014; Guobin et al, 2005; Peng & Wen, 2010). These studies used initial DBT concentrations similar to those used in the work presented here and found, as seen here with both DBT and DBTS, large decreases in residual DBT during culturing.…”
Section: Discussionmentioning
confidence: 99%
“… GC-FID: GC-FID for quantitative estimation of DBT removal [19] and estimation of sulfur compounds by GC-FID-CP-Sil5CB [20].  GC-FPD: such as GC-14A connected with a column Zebron ZB-1 and an FPD for analysis of the content of DBT and its compounds in the culture [21].…”
Section: Speciation Of Concentrations Of Hcssmentioning
confidence: 99%
“…Rhodococcus strains, such as R. erythropolis , have been isolated from contaminated soil using basal salts or sulfur-free medium (Jarullah, 2012). Other isolates, such as Gordonia sp., Noocaria sp., Pantoea agglomerans , Pseudomonas delafieldii , Pseudomonas aeruginosa , SRB, and Sphingomonas subarctica , have also been prepared and studied ( Chen et al ., 2019a , 2019b ; Gunam et al ., 2021a , 2021b ; Saeed et al ., 2022 ).…”
Section: Isolation and Identification Of Microorganismsmentioning
confidence: 99%